2009
DOI: 10.1039/b904984c
|View full text |Cite
|
Sign up to set email alerts
|

Inkjet formation of unilamellar lipid vesicles for cell-like encapsulation

Abstract: Encapsulation of macromolecules within lipid vesicles has the potential to drive biological discovery and enable development of novel, cell-like therapeutics and sensors. However, rapid and reliable production of large numbers of unilamellar vesicles loaded with unrestricted and precisely-controlled contents requires new technologies that overcome size, uniformity, and throughput limitations of existing approaches. Here we present a high-throughput microfluidic method for vesicle formation and encapsulation us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
81
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(83 citation statements)
references
References 32 publications
0
81
1
1
Order By: Relevance
“…Planar lipid bilayers can be created at the interface between two aqueous droplets that are initially surrounded by oil (containing dissolved lipids) and then brought into contact, an approach pioneered by Bayley et al to study membrane pores (29). We have previously demonstrated that these planar bilayers can be deformed by microfluidic jetting with a piezoelectric inkjet nozzle to form giant unilamellar vesicles (26). However, our previous use of lipids dissolved in oil prevented the inclusion of physiologically important signaling lipids.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Planar lipid bilayers can be created at the interface between two aqueous droplets that are initially surrounded by oil (containing dissolved lipids) and then brought into contact, an approach pioneered by Bayley et al to study membrane pores (29). We have previously demonstrated that these planar bilayers can be deformed by microfluidic jetting with a piezoelectric inkjet nozzle to form giant unilamellar vesicles (26). However, our previous use of lipids dissolved in oil prevented the inclusion of physiologically important signaling lipids.…”
Section: Resultsmentioning
confidence: 99%
“…A first step toward engineering systems that recapitulate the physical boundary conditions of cells is encapsulation of components in giant vesicles of controlled lipid chemistry. Several recent microfluidic techniques (22,(24)(25)(26)(27) have achieved formation of giant vesicles with controlled contents using oil-water interfaces to define lipid membranes. However, these techniques form the membranes from lipids dissolved in oil and are incompatible with many biologically important lipids that display poor solubility in oil due to their net charge or saturated fatty acid tails.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the as formed vesicles often lack monodispersity and/or the product yield is relative low. More recently, new techniques such as pulsed jet flow [17,18] and, with the development of soft lithographic methods [19], microfluidic devices have been applied in the formation of lipid vesicles. In particular, microfluidics, i.e., the manipulation of fluids on the micrometric scale, has proven an excellent technique for generating double emulsion for GUV encapsulation.…”
Section: Introductionmentioning
confidence: 99%
“…The size of liposomes can also be tuned by subsequent procedures such as swelling [17], extrusion [18], emulsion, sonication [19], electroformation [20], inkjet formation [21], microfluidic jet [22,23] freeze thaw cycles [24]. Sonication and extrusion are the two most popular techniques.…”
mentioning
confidence: 99%